(untitled) (Nonconventional Technologies Review, 2022)
Electrochemical machining is usually included in the wider group of non-conventional machining methods. This method is based on the material removal from the workpiece as a result of chemical reactions between the electrolyte and the material of the workpiece, under conditions where the tool electrode and the workpiece are immersed in an electrolyte and connected to the poles of a direct current source. Using principles from axiomatic design, specialized equipment was designed. This equipment could be used to experimentally investigate the influence of working gap size on the material removal rate from a test sample made of an electroconductive material. The development of the design matrix led to the observation that, in the proposed version, the condition imposed by the first axiom is not strictly respected. This requires the independence of the functional requirements valid for different components of the equipment, which means that there are possibilities for future improvement of the proposed constructive solution.